(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2026)
Astilbe rivularis is a rare plant with numerous traditional medicinal values, predominantly found in North America and Asia. For centuries, A. rivularis has been traditionally employed in regional ethnomedicinal practices to address several health issues. It contains various phytochemicals, such as alkaloids, coumarins, flavonoids, and glycosides, and is recognised for its diverse biological properties, including antimicrobial, anti-inflammatory, antioxidant, and antidiabetic activities. However, research on this plant and its role in diabetic complications remains limited. Moreover, phytoconstituents present in A. rivularis might be promising candidates for the treatment of diabetic complications involving oxidative stress, the polyol pathway, the PKC-DAG pathway, the hexosamine pathway, and the formation of advanced glycation end-products (AGEs). Therefore, in silico studies were performed targeting RAGE (receptor for AGE), aldose reductase (ALR), and sorbitol dehydrogenase (SDH), which revealed significant interactions with bioactive compounds from A. rivularis, emphasising the potential of this plant for the development of therapeutic strategies to manage diabetes-associated complications. This article presents a narrative review supported by in silico analyses, primarily focusing on the pharmacognostic, phytochemical, and ethnopharmacological attributes of A. rivularis, while further exploring its potential relevance in the context of diabetic complications.